The Practical Decision Maker : a handbook for decision making and problem solving - Harvey, Thomas R.; Corkrum, Sharon M.; Fox, Shari L.; Gustafson, David C.; Keuilian, Deanna K. (Lanham : Rowman & Littlefield, 2022)
"The Practical Decision Maker identifies six steps essential to strong decision-making. Mind-set, problem definition, solution criteria, possible solutions, solution choice, and implementation are depicted along with concrete examples of each. 53 structuring devices are included to help readers move through each step of the decision-making process"--
Includes bibliographical references.
Keywords: Decision making; Problem solving; Management; Leadership